2020
DOI: 10.1002/adfm.202005422
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Self‐Pumping Composite Wound Dressings with Micropore Array Modified Janus Membrane for Enhanced Diabetic Wound Healing

Abstract: Treatment of chronic wounds such as diabetic wounds with large volumes of biofluids is a significant clinical challenge due to ischemia caused by localized edema. To alleviate edema and stimulate angiogenesis, a four-layer composite dressing is designed with a micropore array modified Janus membrane for selfpumping and bioactive ion backflow, a superabsorbent layer for high capacity water absorption, and a bioactive layer containing bioglass for stimulating angiogenesis. The modified Janus membrane not only al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 35 publications
(27 reference statements)
0
82
0
2
Order By: Relevance
“…Currently, various technologies, especially multifunctional systems (including photothermal therapy (PTT), layer-bylayer (LBL) self-assembly technique and 3D-printing technology), are widely used in diabetic wound repair. [248][249][250][251] Photothermal Therapy…”
Section: Other Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, various technologies, especially multifunctional systems (including photothermal therapy (PTT), layer-bylayer (LBL) self-assembly technique and 3D-printing technology), are widely used in diabetic wound repair. [248][249][250][251] Photothermal Therapy…”
Section: Other Technologymentioning
confidence: 99%
“… Not only allows wound exudates transport from wound bed to the dressing, but also enables controlled backflow of bioactive ion containing fluid to the wound bed for stimulating angiogenesis. [ 251 ]
Figure 5 The major applications of nanoparticles.
…”
Section: Technologymentioning
confidence: 99%
“…High glucose exposure interferes with the stability of hypoxia-inducible factor-1, leading to the failure of diabetic wound to up-regulate vascular endothelial growth factor (VEGF) in response to soft tissue ischemia, resulting in impaired angiogenesis [ 24 ]. Previous studies have shown that BG can release Si ions to promote angiogenesis [ 13 ]. In addition, studies have shown that diabetic wound is often the most suitable place for microbial colonization, because of its hyperglycemia, which can easily give rise to wound infection [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, direct contact with BG may adhere to the wound bed, causing laceration and other adverse reactions of wound [ 13 ]. Hydrogel is a hydrophilic polymer with intrinsic three-dimensional structure [ 14 ], which could release of therapeutic molecules as attractive alternatives to many systems approaches [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cell experiments showed that the electrospun scaffolds with slow ions release promoted the proliferation of human umbilical vein endothelial cells, indicating that the bioactivity of the composite scaffolds could be regulated by adjusting ions release behavior to obtain optimal bioactivity for tissue engineering applications. Key words: calcium silicate; electrospun; controllable release; degradation; electrospray 静电纺丝支架因具有类细胞外基质的三维结构、 大比表面积、 高孔隙率 [1][2][3] , 被广泛应用于血管 [4][5] 、 心肌 [6][7] 、神经 [8][9] 等组织工程创伤修复 [10] 领域。电 纺丝支架经过多年的研究发展,通过在其中引入活 性药物 [11] 和活性陶瓷等 [12] 赋予了电纺丝支架粘附、 增殖、迁移、分化等生物活性。 硅酸钙等生物活性陶瓷分解释放的 SiO3 2-,不 仅被证实具有促进骨 [13] 、牙齿 [14] 等硬组织再生的作 用,近年来陆续发现 SiO3 2-还具有促进血管 [15] 、脂 肪 [16] 、皮肤创面 [17] 、毛囊 [18] 、心肌 [19] 等多种软组织 修复的生物活性。前期研究中,硅酸钙等生物活性 陶瓷通过混纺 [19] 或者喷涂 [20] 的方式与电纺丝进行 复合,促进了组织的修复。但是,不同的组织修复 所需的活性 SiO3 2-浓度范围各有差异 [21] ,以促进成 血管性能为例,据 Li 等 [22] 材料的亲疏水性可影响环境中的液体扩散到材 料内部的速率,继而影响后续释放过程 [23,29] [32] , CSH@ES 小孔径支架的第 1 天释放的离子 浓度反而较低,待高分子部分降解后,离子释放才 逐渐增多;而在大孔径支架中,由于表面亲水性较 强,孔径越大水分子扩散速度越快 [33] [34] 报道,孔隙率由电纺丝的直 径和孔径决定,因此孔隙率也无显著性差异。在力 学性能方面,根据前期研究报道,电纺丝中掺入 1%CSH 纳米线后,各力学参数以及应力-应变曲线 无明显变化 [19] ,掺入 10%以上 CSH 纳米线才能显 著提高电纺丝的拉伸强度 [35] ,而本研究中加入的…”
unclassified